Producer service linkages and city connectivity in the mega-city region of China: A case study of the Pearl River Delta. (October 2015) - Yeh, Anthony GO; Yang, Fiona F; Wang, Jiejing
This paper examines the intra- and inter-firm producer service linkages and city connectivity of the Pearl River Delta (PRD), one of the fastest growing and globalising mega-city regions in China. The study reveals that the rapid growth of producer services in the recent two decades has emerged as a crucial contributor to the formation of the regional network that was previously shaped mainly by manufacturing activities. To provide a better understanding of the mechanisms of mega-city regions, a nexus between the literature on globalisation and mega-city regions and the studies on the service economy must be developed to consider not only intra-firm office connections, but also the linkages of producer services between different firms and economic sectors. Through a questionnaire survey covering 1020 producer service firms in three major PRD cities, we provide evidence that in a manner different from manufacturing activities, producer services linkages, both intra-firm and inter-firm, bind the cities into a hierarchical and localised regional system.